Kualitas Pelayanan Usaha Mikro Kecil Dan Menengah (UMKM) Pada Bank BCA Cabang Tanah Abang - SARAH; Mawar (Jurnal Administrasi Publik dan Pemerintahan, 2024)
People's Business Credit is credit or financing provided by banking companies including BCA Bank to Micro, Small and Medium Enterprises (MSMEs) with the aim of improving and expanding the Bank's services to productive MSMEs. This research was conducted to determine the quality of MSME services. This research uses descriptive qualitative methods. Data collection methods were obtained using observation and interview methods. Analysis of research results using Parasuman, Zeithaml, and Berry theories, namely Reliability, Responsiveness, Assurance, Emphaty, Tangible. The results of the research show that the quality of MSME services provided by Bank Central Asia Tanah Abang Branch is optimal, namely, Responsiveness, Assurance and Emphaty customers show satisfaction related to the absence of administration costs and provision costs and credit financing employees are able to answer complaints and provide appropriate suggestions. According to the problems and needs of MSME players. Meanwhile, Tangibles and Customer Reliability show the opposite, namely that there is no special waiting room for MSME financing applications and the requirements that must be attached are still quite complicated, such as having a business of at least 6 months and being required to have a Business Certificate and Business License Number